Changes in foveal avascular zone area and retinal vein diameter in patients with retinal vein occlusion detected by fundus fluorescein angiography - Liao, Dingying; Zhou, Zixia; Wang, Fei; Zhang, Bin; Wang, Yanfen; Zheng, Yuping; Li, Jinying (Frontiers in Medicine, 2023)
Purpose To investigate changes in foveal avascular area (FAZ) and retinal vein diameter in patients with retinal vein occlusion (RVO) after intravitreal ranibizumab, and to analyze the correlation between ranibizumab therapy and visual gain. Methods This retrospective study enrolled 95 eyes of 95 patients who had accepted three consecutive monthly ranibizumab injections, including 50 branch RVOs (BRVOs) and 45 central RVOs (CRVOs). BRVOs were divided into ischemia group (n = 32) and non-ischemia group (n = 18), and CRVOs also had ischemia group (n = 28) and non-ischemia group (n = 17). Comprehensive ophthalmic examinations were performed before the first injection and after 6, 12, and 24 months. The FAZ was manually circumscribed on early-phase images of fundus fluorescein angiography. Retinal vein diameters were measured on fundus photographs. Results After three injections, the FAZ area was significantly enlarged firstly and then reduced in all ischemic RVOs and the non-ischemic BRVOs (p < 0.05), while the retinal vein diameter was significantly reduced firstly and then increased in all groups except for unobstructed branch veins of non-ischemic BRVOs (p < 0.05). The correlation between the FAZ area and best corrected visual acuity was statistically significant in all CRVOs (non-ischemic, r = 0.372; ischemic, r = 0.286; p < 0.01) and ischemic BRVOs (r = 0.180, p < 0.05). Spearman’s correlation analysis revealed that the retinal vein diameter was significantly correlated to the larger FAZ area in obstructed branch veins of ischemic BRVOs (r = −0.31, p < 0.01), inferior temporal branch veins of non-ischemic CRVOs (r = −0.461, p < 0.01) and ischemia CRVO groups (superior temporal branch vein, r = −0.226, p < 0.05; inferior temporal branch vein, r = −0.259, p < 0.01). Conclusion After three consecutive monthly ranibizumab injections, the FAZ area was enlarged and retinal vein diameter reduced with gradual recovery to near baseline from 12 months. These results suggest that ranibizumab therapy can worsen macular ischemia and prevent visual gain in the short term. It has important significance for the treatment and prognosis of RVO, although the natural course of RVO may also affect ischemia and visual gain.